Continuous Running vs. Interval Training on VO2Max Increase in 16-17-Year-Old Football Athletes at Bintang Kejora Football School Deli Serdang Regency - Reyhan Varian Savero; Imran Akhmad (Journal of Indonesian Active in Sports, 2024)
This study compares the Vo2Max effects of continuous running and interval training on 16-17-year-old football participants at Bintang Kejora football school in Deli Serdang Regency in 2022. The research method is experimental quantitative research. This study used purposive sampling to pick Bintang Kejora football school athletes under certain conditions. The study lasted six weeks with three training sessions per week. The statistical analysis of Vo2Max increase in the continuous running group showed a tcount of 6.56 and a ttable of 2.75, with Î± = 0.05. We reject H0 and accept Ha since the tcount is bigger than the ttable (6.56 > 2.75). In 2022, the continuous running exercise group improved the Vo2Max results of 16-17-year-old football participants at Bintang Kejora football school (SSB), Deli Serdang Regency. Hypothesis II on interval training's Vo2Max rise had a tcount value of 6.11, higher than the crucial ttable value of 2.75. This means H0 is rejected and Ha is accepted. Thus, the interval training group affects the Vo2Max results of 16“17-year-old football participants at Bintang Kejora in Deli Serdang Regency. Upon assessing hypothesis III, the average standard deviation tcount value was 1.32, while the ttable value was 2.23, with Î± = 0.05. Low tcount values (tcount < ttable) support the null hypothesis (H0) and reject the alternative hypothesis (Ha). This analysis suggests that continuous running or interval training have similar effects on Vo2Max outcomes for 16-17-year-old football players at the Bintang Kejora football school in Deli Serdang Regency.